The Phenomenon of Synonymy in Communicative Phraseological Units - Ruzikulova Gulirukhsor Gofur kizi (Researchparks Publishing, 2021)
This article analyzes the phenomenon of synonymy of phaseological units and proverbs in Uzbek and English. It has been studied that proverbs have a feature that distinguishes them from other phraseological units, Structurally proverbs have a sentence structure with complete syntactic integrity. There are also examples of proverbs that express the content of advice, wisdom, education and aphorisms, and reflect the national cultural semantics.